Developing Leaders: Implementation of a Peer Advising Program for a Public Health Sciences Undergraduate Program - Griffin, Megan; DiFulvio, Gloria T.; Gerber, Daniel Shea (Frontiers in Public Health, 2015)
Peer advising is an integral part of our undergraduate advising system in the Public Health Sciences major at the University of Massachusetts Amherst. The program was developed in 2009 to address the advising needs of a rapidly growing major that went from 25 to over 530 majors between 2007 and 2014. Each year, 9-12 top performing upper-level students are chosen through an intensive application process. A major goal of the program is to provide curriculum and career guidance to students in the major and empower students in their academic and professional pursuits. The year-long program involves several components, including: staffing the drop-in advising center, attending training seminars, developing and presenting workshops for students, meeting prospective students and families, evaluating ways to improve the program, and collaborating on self-directed projects. The peer advisors also provide program staff insight into the needs and perspectives of students in the major. In turn, peer advisors gain valuable leadership and communication skills, and learn strategies for improving student success. The Peer Advising Program builds community and fosters personal and professional development for the peer advisors. In this paper, we will discuss the undergraduate peer advising model, the benefits and challenges of the program, and lessons learned. Several methods were used to understand the perceived benefits and challenges of the program and experiences of students who utilized the Peer Advising Center. The data for this evaluation were drawn from three sources: 1) archival records from the Peer Advising Center; 2) feedback from peer advisors who completed the year-long internship; and 3) a survey of students who utilized the Peer Advising Center. Results of this preliminary evaluation indicate that peer advisors gain valuable skills that they can carry into their professional world. The program is also a way to engage students in building community within the major.